The Utilization of Rice Straw for Increase Orange Productivity and Reducing Environmental Pollution - Rifiana Rifiana; Hamdani Hamdani (TROPICAL WETLAND JOURNAL, 2020)
Siam Banjar oranges was one of the leading commodities in South Kalimantan with an area 2,594 ha, 113,-149 tons of production and 43.72 ha-1 of productivity (Department of Agriculture South Kalimantan, 2006 in www.kalselprov.go.id/). The development of Siam Banjar oranges in South Kalimantan was overflow in Barito Kuala and Banjar District. The level of responsiveness plants for fertilization encourages farmers to apply high inorganic fertilizers. If it is applied continuously and without return organic matter into the soil, it will produce the reduced soil fertility in terms of chemical, physical, and biological soil. This research showed the effect of the use of straw in increasing the production of Siam Banjar oranges. First, they completely decomposed so that increasing soil fertility. Second, reduce environmental pollution because it did not leave residues as inorganic fertilizers. Third, prevent soil erosion so that nutrients needed by oranges for grow properly could be fulfilled optimally. So, oranges did not easily attacked by pests and diseases then provide abundant harvest. The results of the differences between two values ​​could be concluded that, the benefits of orange farming was produced with straw was greater than farming without straw. Revenue Cost Ratio (RCR) value of orange farming with straw was 3.56 and the Revenue Cost Ratio (RCR) value of orange farming without straw was 3.26. Based on the RCR value, orange farming with straw was more feasible than orange farming without a straw.